Polypharmacy Leading To Adverse Drug Reactions In Elderly In A Tertiary Care Hospital - AYESHA ROMANA; LAXMINARAYANA KAMATH; ASTHA SARDA; SUSHMA MURARAIAH; JAYANTHI CR (International Journal of Pharma and Bio Sciences, 2012)
Polypharmacy is a common occurrence in elderly patients due to reasons like multiple co-morbidities and multiple prescribing physicians. The present study was designed to identify the adverse drug reactions occurring in the elderly as a result of polypharmacy and also to assess the rationality of prescription based on World Health Organization (WHO) criteria and Beer’s criteria. This study was conducted at Victoria hospital attached to Bangalore Medical College and Research Institute . Hundred patients aged ≥60 years and prescribed more than 5 drugs were included in the study. The analysis of data revealed, the number of drugs per prescription was 8.42±2.4. Of the total 842 drugs prescribed, number of drugs prescribed by generic name was 36 (4.27%) and number of drugs prescribed from WHO model list of essential medicine was 444 (52.7%). Adverse drug reactions were mainly seen in 15% of patients. 20 patients were prescribed potentially harmful drugs according to Beer’s list. To conclude, polypharmacy was seen in majority of elderly patients but the use of injections and antibiotics were limited. Prescribing by generic name and from essential drug list needs to be improved. Many ADRs were noted for commonly prescribed drugs and also for inappropriate drugs as given in Beer’s list.